TP53 modulates radiotherapy fraction size sensitivity in normal and malignant cells - Anbalagan, Selvakumar; Ström, Cecilia; Downs, Jessica A.; Jeggo, Penny A.; McBay, David; Wilkins, Anna; Rothkamm, Kai; Harrington, Kevin J.; Yarnold, John R.; Somaiah, Navita (Scientific reports, 2021)
Recent clinical trials in breast and prostate cancer have established that fewer, larger daily doses (fractions) of radiotherapy are safe and effective, but these do not represent personalised dosing on a patient-by-patient basis. Understanding cell and molecular mechanisms determining fraction size sensitivity is essential to fully exploit this therapeutic variable for patient benefit. The hypothesis under test in this study is that fraction size sensitivity is dependent on the presence of wild-type (WT) p53 and intact non-homologous end-joining (NHEJ). Using single or split-doses of radiation in a range of normal and malignant cells, split-dose recovery was determined using colony-survival assays. Both normal and tumour cells with WT p53 demonstrated significant split-dose recovery, whereas Li-Fraumeni fibroblasts and tumour cells with defective G1/S checkpoint had a large S/G2 component and lost the sparing effect of smaller fractions. There was lack of split-dose recovery in NHEJ-deficient cells and DNA-PKcs inhibitor increased sensitivity to split-doses in glioma cells. Furthermore, siRNA knockdown of p53 in fibroblasts reduced split-dose recovery. In summary, cells defective in p53 are less sensitive to radiotherapy fraction size and lack of split-dose recovery in DNA ligase IV and DNA-PKcs mutant cells suggests the dependence of fraction size sensitivity on intact NHEJ.